PENGARUH PENGETAHUAN DAN PERAN SERTA PETUGAS KESEHATAN DENGAN KEPATUHAN IBU HAMIL TRIMESTER I TERHADAP CAPAIAN KUNJUNGAN PERTAMA (K1) - Anggraini, Helni; Nati Indriani, Putu Lusita (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background: The first visit (K1) is the first contact of pregnant women with health workers to get health checks and health services in the first trimester, where the gestational age is 1 to 12 weeks. Objective: To correlate knowledge and participation of health workers simultaneously with the compliance of pregnant women in the first trimester to the achievement of the first visit (K1). Methods: This study uses a quantitative analytical survey research design with a cross sectional approach, which is a study to study the dynamics of the relationship between the independent variable and the dependent variable, using a cross sectional approach where the independent variables are Knowledge, Role of Health Officers and the dependent variable is Obedience in First Trimester Pregnant Women. Results: The results of the univariate analysis showed respondents who made the first visit (50%), good knowledge (53.6%) and the role of health workers (46.4%). The statistical test used is the chi-square test. The results of the bivariate analysis showed that there was a significant relationship between knowledge (PValue = 0.016 > = 0.05), the role of health workers (PValue = 0.003 > = 0.05) on first visit achievement (K1). Conclusion : There is a significant relationship between the knowledge and participation of health workers with the First Visit Achievement (K1) Keywords: Knowledge, the role of health workers and pregnant women in the 1st trimester